Acidogenesis of cellulosic hydrolysates for new generation biofuels. (August 2016) - Kandylis, Panagiotis; Bekatorou, Argyro; Pissaridi, Katerina; Lappa, Katerina; Dima, Agapi; Kanellaki, Maria; Koutinas, Athanasios A.
Abstract: This article presents a comprehensive review on hydrolysis and acidogenesis of lignocellulosic waste biomass and makes clear new perspectives in biofuel research. Specifically, the acidogenesis of lignocellulosics and liquid effluent have been discussed extensively with potential goal the production of a new generation biofuel. This new biofuel can be produced through esterification of volatile fatty acids with ethanol (produced simultaneously during the acidogenesis) or/and with another alcohol. That will overcome the major problems faced during bioethanol production and concerns the high energy demand of the bioethanol production plant. Specifically, it was found that the main volatile fatty acids formed are formic, acetic, propionic, butyric, lactic and valeric. Their formation depends on NADH/NAD+ proportion and on conditions such as pH, organic load and chemical composition of the waste is treated. These conditions look to affect microorganisms survival and the formation of predominant acetic, butyric and lactic acid. The use of γ-alumina promotes the formation of volatile fatty acids simultaneously with bio-ethanol. Highlights: The composition of VFAs can be programmed with pH, organic load and waste used. The VFA that will predominate depends on NADH/NAD+ proportion. γ-alumina promotes VFAs formation simultaneously with bio-ethanol. New research opens for searching promoters in acidogenesis. The differentiation of VFAs depends on the microorganisms that will predominate.